Atomic level termination for passivation and functionalisation of silicon surfaces. Issue 33 (13th August 2020) - Grant, Nicholas E.; Pointon, Alex I.; Jefferies, Richard; Hiller, Daniel; Han, Yisong; Beanland, Richard; Walker, Marc; Murphy, John D.
Abstract : The termination of silicon surfaces is studied from the nanometre to the centimetre scale, with differences in behaviour between hydrogen and fluorine terminated surfaces persisting after some subsequent surface passivation treatments. Abstract : Chemical treatments play an essential role in the formation of high quality interfaces between materials, including in semiconductor devices, and in the functionalisation of surfaces. We have investigated the effects of hydrogen and fluorine termination of (100)-orientation silicon surfaces over a range of length scales. At the centimetre scale, lifetime measurements show clean silicon surfaces can be temporarily passivated by a short treatment in both HF(2%) : HCl(2%) and HF(50%) solutions. The lifetime, and hence surface passivation, becomes better with immersion time in the former, and worse with immersion time in the latter. At the nanometre scale, X-ray photoelectron spectroscopy and atomic force microscopy show treatment with strong HF solutions results in a roughened fluorine-terminated surface. Subsequent superacid-derived surface passivation on different chemically treated surfaces shows considerably better passivation on surfaces treated with HF(2%) : HCl(2%) compared to HF. Lifetime data are modelled to understand the termination in terms of chemical and field effect passivation at the centimetre scale. Surfaces passivated with Al2 O3 grown by atomic layer deposition behave similarly when either HF(2%) : HCl(2%) or HF(50%) are used as a pre-treatment, possibly because of the thin silicon dioxide interlayer which subsequently forms. Our study highlights that chemical pre-treatments can be extremely important in the creation of high quality functionalised surfaces.